JunB contributes to Id2 repression and the epithelial–mesenchymal transition in response to transforming growth factor–β - Gervasi, Megan (The Rockefeller University Press, 2012)
The process of epithelial–mesenchymal transition (EMT) in response to transforming growth factor–β (TGF-β) contributes to tissue fibrosis, wound healing, and cancer via a mechanism that is not fully understood. This study identifies a critical role of JunB in the EMT and profibrotic responses to TGF-β. Depletion of JunB by small interfering ribonucleic acid abrogates TGF-β–induced disruption of cell–cell junctions, formation of actin fibers, focal adhesions, and expression of fibrotic proteins. JunB contributes to Smad-mediated repression of inhibitor of differentiation 2 through interaction with transcription repressor activating transcription factor 3. Importantly, JunB mediates the TGF-β induction of profibrotic response factors, fibronectin, fibulin-2, tropomyosin (Tpm1), and integrin-β3, which play critical roles in matrix deposition, cell–matrix adhesion, and actin stress fibers. In summary, JunB provides important input in setting the transcriptional program of the EMT and profibrotic responses to TGF-β. Thus, JunB represents an important target in diseases associated with EMT, including cancer and fibrosis.